(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
Creative accounting is a new approach to accounting that aims to foster greater creativity and innovation in financial processes. It focuses on transforming traditional financial data into valuable strategic information to aid decision-making. Furthermore, organizational efficiency measures the effectiveness and efficiency of a company in achieving its goals. The relationship between creative accounting and organizational efficiency lies in how creativity and innovation in accounting are used to improve overall organizational efficiency. For example, the use of innovative accounting techniques can improve decision-making processes and increase business efficiency, positively impacting an organization’s performance throughout the year. Creative accounting is a set of accounting procedures and activities that exploit legal loopholes to improve a company’s image. This is done by manipulating actual figures in a company’s financial statements and special reports. Corporate accountants use these methods to achieve personal gain or, at the behest of management, to obtain fictitious or unrealistic profits. Manipulating accounting data by exploiting loopholes in accounting principles and standards leads to beautifying a company’s image and glorifying its profitability. It is worth noting that legal creative accounting is not subject to legal accountability unless it influences public opinion by misleading investors with information that leads to poor decision-making. Creative accounting techniques include overstating revenues at a rate expected to actual values, understating the cost of destroying assets through capitalization, overstating deferred costs, hiding liabilities, and manipulating inventory. The accountant is responsible for reviewing the records and accounts related to all activities that fall under creative accounting, such as sales, cost of goods sold, expenses, operating cash, and accounts receivable. It must prioritize the reliability of accounting information and compliance with legal and ethical standards of organizations in order to maintain their integrity and organizational success.